2020
DOI: 10.3390/nu12030746
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health-Related Quality of Life and Nutritional Status in Adult Patients with Crohn’s Disease

Abstract: This study aimed to assess health related quality of life (HRQoL) in adult patients with Crohn’s disease (CD), considering disease severity and gender differences, and also its relationship with nutritional status. Consecutive adult patients aged 18–65 years with CD were recruited. Disease activity was clinically defined by the Crohn’s Disease Activity Index (CDAI) in active and quiescent phases. HRQoL was evaluated using the validated short form (SF)-36 questionnaire for the Italian population. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…The impact of previous surgery due to medically refractory disease or disease complications has been considered as a factor influencing HRQoL. A lower HRQoL was documented in patients who experienced surgery for their disease compared to those free of surgery, and these data are supported by results obtained in the Italian population [40]. In addition, European data demonstrated that patients with UC who underwent surgery had significantly poorer disease-specific and generic quality of life during follow-up when compared to other UC patients who did not experience surgery [26].…”
Section: Discussionmentioning
confidence: 78%
“…The impact of previous surgery due to medically refractory disease or disease complications has been considered as a factor influencing HRQoL. A lower HRQoL was documented in patients who experienced surgery for their disease compared to those free of surgery, and these data are supported by results obtained in the Italian population [40]. In addition, European data demonstrated that patients with UC who underwent surgery had significantly poorer disease-specific and generic quality of life during follow-up when compared to other UC patients who did not experience surgery [26].…”
Section: Discussionmentioning
confidence: 78%
“…Malnutrition has negative effects on IBD patients and can reduce their quality of life. 22,23 Therefore, nutritional management is very important for IBD patients, although traditional evaluation methods involve blood tests and questionnaires, which are limited by cost, invasiveness, and complex process. Recent studies have evaluated whether body composition testing can supplement the traditional blood tests and questionnaires in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…W badaniach tych zaobserwowano większą akceptację choroby i wyższe poczucie satysfakcji życiowej u osób bez objawów chorobowych, w fazie remisji. W tym zakresie zauważa się zbieżność wyników [8,9,11,19]. Doniesienia różnych autorów wskazują, że leczenie choroby niewymagające interwencji chirurgicznej korzystnie rzutuje na ogólne funkcjonowanie jednostki [9].…”
Section: Dyskusjaunclassified